Dual-band dual-linearly polarized multibeam transmit-reflect-array antenna with independent beams control - Wei Luo; Liu Luo; Xiaoxue Wang; Min Wang; Hongsheng Zhang (Alexandria Engineering Journal)
In this paper, a dual-band, dual-linearly polarized multibeam transmit-reflect-array (TRA) antenna is proposed. The dual-beams with different polarizations can be transmitted in the lower frequency band and reflected in the higher frequency band. The element comprises three metallic layers separated by substrate, enabling independent control of vertically and horizontally polarized waves in both the reflective and transmissive bands. Due to the frequency and polarization independence of the element, phase compensations are designed for vertically and horizontally polarized waves in each band, respectively. The circular aperture TRA is illuminated with a rotated linearly polarized horn, thereby generating dual-beams with different directions and polarizations in both the transmissive and reflective modes. The measurement results show that the peak aperture efficiency is 43.6 % and 36.0 % for the reflection band and transmission band. For the transmission band, the 3 dB gain bandwidths are 11.2 % (21–23.5 GHz) for horizontal polarization and 16.1 % (20–23.5 GHz) for vertical polarization. The 3 dB gain bandwidths for the reflection band are 12.1 % (27–30.5 GHz) for both the horizontal and vertical polarizations. The TRA antenna emerges as a promising contender for the implementation of bidirectional wireless communication.